Fabrication and Biodegradability of Starch Cell-Plastics as Recyclable Resources - Akihito Nakanishi; Kohei Iritani; Yuri Sakihama; Marina Watanabe; Ayano Mochiduki; Akane Tsuruta; Syunta Sakamoto; Ayami Ota (Applied Sciences, 2021)
Recently, cell-plastics, which are composed of unicellular green algal cells and biodegradable compounds as ingredients and fillers, have been suggested as carbon-recyclable materials instead of petroleum-based plastics. In this study, cell-plastics, fabricated with Chlamydomonas reinhardtii as an ingredient and a mixture of two types of starches (raw and oxidized starches) as a filler, were successfully stabilized as independent structures despite the quantity of algal cells being nine times more than that of starch. All starch cell-plastics were water repellent, possibly due to their bumpy surface structures. The starch cell-plastic, composed of 50% cells and 50% starch (1.5:1 of oxidized starch versus raw starch), showed 327 ± 52 MPa as Young’s modulus and 6.45 ± 1.20 MPa as tensile strength, indicating the possibility to be a suitable replacement for petroleum-based plastics. Additionally, all starch cell-plastics showed water-repellency and maintained those structures dipped in phosphate-buffered saline buffer as a water environment for 24 h, meaning that all starch cell-plastics had evaluable water resistance. On the other hand, by adding α-amylase, all starch cell-plastics were collapsed and lost the weight efficiently, indicated their biodegradability. This is the first paper to describe starch cell-plastics from their fabrication to biodegradation.